Multi-province epidemiological research studies using administrative data in Canada: challenges and opportunities - Amanda Leanne Butler; Mark Smith; Wayne Jones; Carol E Adair; Simone Vigod; Paul Kurdyak; Alain Lesage (International Journal of Population Data Science, 2018)
Background: Canada has a publicly-funded universal health care system with unique information systems managed by 13 different provinces and territories. This context creates inconsistencies in data collection and challenges for research or surveillance conducted at the national or multi-jurisdictional level.